Formulation, Optimization and Characterization of PLGA-Chitosan Nanoparticles Containing Vinorelbine Ditartrate - Bandil, Varsha; Gupta, Jeetendra Kumar; Goyal, Manoj Kumar (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: The prime objective of our investigation was to optimize PLGA-chitosan nanoparticles containing vinorelbine ditartrate. Materials and Methods: The Vinorelbine ditartrate nanoparticles were formulated using emulsion method followed by probe sonication to reduce the size. A three factor three level Box-Behnken Design has been implemented to optimize chitosan, Poloxamer 188 and sonication time (independent variables) for particle size, polydispersity index and entrapment efficiency (%) as the measured responses. Particle size, zeta potential, surface morphology, entrapment effectiveness, and in vitro drug release were all evaluated for the optimised formulation. Results: The optimized PLGA-chitosan nanoparticle exhibited particles size of 161.22 nm with polydispersity index of 0.229 and zeta potential value of 10.99 mV. The formulation exhibited 78.9% entrapment of vinorelbine ditartrate. The nanoparticle was able to sustain the release of vinorelbine for more than 140 hr in the in vitro release studies. Conclusion: From studying the obtained results, it could be concluded from the investigation that PLGA-chitosan nanoparticles could be good approach to improve the bioavailability of the entrapped drug.
Keywords: Nanoparticles; Vinorelbine ditartrate; Particle size; Optimization; in vitro drug release